Foliar water uptake by coastal wetland plants: A novel water acquisition mechanism in arid and humid subtropical mangroves. (15th May 2020) - Hayes, Matthew A.; Chapman, Samantha; Jesse, Amber; O'Brien, Elizabeth; Langley, J. Adam; Bardou, Remi; Devaney, John; Parker, John D.; Cavanaugh, Kyle C.
Abstract: Climate change alters freshwater availability in many ecosystems leading to shifts in distributions for many plants. Despite living exclusively in intertidal, saline environments, mangroves rely on non‐saline water to maintain plant productivity. However, several mangrove species persist in arid environments where non‐saline water from rain and groundwater sources are limited. Under these conditions, foliar water uptake from fog and mist may be an important water acquisition strategy. We conducted a field experiment in arid Baja California Sur, Mexico along with a controlled mist chamber experiment (using seedlings sourced from humid subtropical region, Florida, USA) to show that three co‐occurring, neotropical mangrove species, Avicennia germinans, Laguncularia racemosa and Rhizophora mangle, growing in both arid and humid environments can access water condensed on their leaves. Foliar water uptake was greatest in A. germinans and lowest in R. mangle, possibly reflecting leaf traits associated with species‐specific water balance strategies. In our field misting experiment, the contribution of foliar water uptake was higher in A. germinans (32 ± 2%) than L. racemosa (26 ± 2%) and R. mangle (16 ± 1%). Foliar water uptake also varied across locations for L. racemosa and R. mangle, with declining uptake towards both species' northern range limits in Baja California Sur, suggesting the distribution patterns of arid‐zone mangroves may be affected by species‐specific spatial variation in foliar water use. Within species, foliar water use was comparable across field and controlled experiments irrespective of source population (Baja California Sur vs. Florida), suggesting foliar water uptake is not an arid‐zone adaptation, and is instead used as a supplemental water balance strategy in arid and humid neotropical mangroves. Synthesis . Our findings indicate mangroves have the potential to access atmospheric water, such as rain, dew and sea fog, through their leaves to offset soil water deficits. Variation in foliar water use across these three neotropical mangrove species may influence mangrove species distributions across arid‐zone and pseudo‐drought (highly saline) environments, with implications for mangrove response to climate change. Abstract : Our findings indicate mangroves have the potential to access atmospheric water, such as rain, dew and sea fog, through their leaves to offset soil water deficits. Variation in foliar water use across these three neotropical mangrove species may influence mangrove species distributions across arid‐zone and pseudo‐drought (highly saline) environments, with implications for mangrove response to climate change.